2009
DOI: 10.1167/iovs.08-2441
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Use of Bevacizumab as an Antifibrotic Agent in Glaucoma Filtration Surgery in the Rabbit

Abstract: Postoperative subconjunctival injection of bevacizumab is associated with improved trabeculectomy bleb survival in the rabbit model. Bevacizumab may be a useful agent for improving success and limiting scar tissue formation after trabeculectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 21 publications
11
69
1
6
Order By: Relevance
“…21 The subconjunctival injection of bevacizumab was found to be associated with improvements in trabeculectomy bleb survival in glaucoma, which suggests that bevacizumab may be a useful agent for improving the success rate and limiting scar tissue formation after trabeculectomy. 22 This study aimed to evaluate the additive effect of bevacizumab to MMC-augmented trabeculectomy in recurrent cases of childhood glaucoma concerning its efficacy and complications. Our results revealed that the mean age was 2.16 ± 1.5 (range 7 months to 4.1 years); this explains the failure of the primary surgery in these children because a younger age results in a lower success rate.…”
Section: Discussionmentioning
confidence: 99%
“…21 The subconjunctival injection of bevacizumab was found to be associated with improvements in trabeculectomy bleb survival in glaucoma, which suggests that bevacizumab may be a useful agent for improving the success rate and limiting scar tissue formation after trabeculectomy. 22 This study aimed to evaluate the additive effect of bevacizumab to MMC-augmented trabeculectomy in recurrent cases of childhood glaucoma concerning its efficacy and complications. Our results revealed that the mean age was 2.16 ± 1.5 (range 7 months to 4.1 years); this explains the failure of the primary surgery in these children because a younger age results in a lower success rate.…”
Section: Discussionmentioning
confidence: 99%
“…В ходе иссле-дования наблюдалось выраженное влияние инги-битора VEGF на морфологические характеристики и функционирование фильтрационной подушки. Результаты гистологических и иммуногистохими-ческих методов подтвердили существенное сни-жение выраженности рубцовых и фиброзных из-менений под влиянием анти-VEGF [50]. В 2010 г. сходное экспериментальное исследование было проведено A.…”
Section: применение ингибиторов Vegf после фистулизирующих антиглаукоunclassified
“…In animal models of trabeculectomy, adjunctive bevacizumab, a monoclonal antibody to VEGF-A, was associated with inhibition of Tenon's fibroblast proliferation, decreased collagen deposition and decreased fibroblast differentiation into myofibroblasts, leading to more favourable bleb morphology and longer bleb survival. [5][6][7][8] Given these encouraging animal model results, we designed a pilot clinical trial using ranibizumab, a Fab fragment of a recombinant humanized immunoglobulin G1k isotype murine monoclonal antibody to VEGF-A. The purpose of our small randomized, controlled trial was to determine whether or not intravitreal ranibizumab therapy before and after Ahmed tube insertion for open-angle glaucoma (OAG) could be a safe method to prevent scar tissue formation and achieve better intraocular pressure (IOP) control.…”
Section: Introductionmentioning
confidence: 99%